Smart Law Application Engineering for Post-Disaster Recovery in Sumatra - Refa Swinta Maharani; Inggrit Fernandes (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Flood disasters frequently occur in West Sumatra and cause multidimensional impacts on micro, small, and medium enterprises (MSMEs). Beyond physical and economic damage, MSMEs face serious administrative and legal challenges, particularly in restoring trademark legality due to lost documents, disrupted archives, and limited access to legal services. These conditions weaken legal protection and reduce business competitiveness during post-disaster recovery. This study aims to engineer a Smart Law application, a digital portal integrated with artificial intelligence (AI), designed to support post-disaster trademark legality recovery for MSMEs in Sumatra. The research employed a research and development (R&D) approach consisting of needs assessment, system design, prototype development, and limited user testing. Data were collected through literature review, regulatory analysis, interviews with disaster-affected MSMEs, and field observations, and analyzed using a qualitative descriptive method. The results indicate that the Smart Law application is capable of delivering structured legal information, contextual guidance, and AI-based preliminary recommendations tailored to MSME conditions. The application functions as an initial legal assistance tool that improves accessibility, efficiency, and understanding of trademark recovery procedures in post-disaster contexts. This study contributes to the development of AI-assisted legal services and digital solutions for MSME resilience in disaster-prone regions.